Teachers' Perceptions of the Principal's Role as a Driver of Educational Quality in the Merdeka Belajar Era - Fauziah Wulansari; Anam Sutopo; Sofyan Anif (Journal of Educational Sciences, 2026)
The transformation of education policy through Merdeka Belajar (Freedom to Learn) positions schools as adaptive learning ecosystems oriented toward sustainable quality. This study aims to examine teachers' perceptions of the principal's role as a driver of educational quality in the implementation of Merdeka Belajar and to identify supporting and inhibiting factors affecting this role. The study used a qualitative descriptive approach supported by simple quantitative data. The study subjects consisted of 17 teachers and one principal at an elementary school implementing Merdeka Belajar. Data were collected through a 4-point Likert-scale questionnaire and written interviews, then analyzed using mean scores, percentage of maximum scores, category interpretation, and thematic analysis. The quantitative results showed an overall mean score of 3.32 out of 4 (82.9%), indicating positive teacher perceptions. The highest score was obtained for professional development support (M = 3.51; 87.8%), followed by support for Merdeka Belajar implementation (M = 3.47; 86.8%), instructional leadership (M = 3.42; 85.5%), and school climate and culture (M = 3.28; 82.0%). However, collaboration among teachers (M = 3.18; 79.5%) and transparency of programs (M = 3.05; 76.3%) were comparatively lower, indicating areas that require strengthening. These findings emphasize that consistent learning-oriented leadership, supported by collaboration and transparent school governance, is essential for sustainable educational quality.